DESIGN OF SUPPORT ALTERNATIVES AND CGT RAMP DOWN CROSS CUT IV STABILITY, L500 GUDANG HANDAK MINE, PT. ANEKA TAMBANG. TBK, UBPE PONGKOR ÃâÃâ WEST JAVA - MARCELL FANDY (NIM : 22110003), PATRICK
Gudang handak mine is one of the underground gold mines of PT. Aneka Tambang.Tbk in Pongkor. Today the mining activity has been concentrated at the level of 500 meters, and as an effort to support the sustainability of the mine, development continues to be done to reach the level of 400 meters. In order to reach this level, a Ramp down has been made, which is an opening as an access to the ore deposits and which has a very vital function. Therefore, when rock conditions are classified as not profitable, supports need to be used. Currently the Ramp down has been using support split set and support H-beam with 1.5-meter distance between each set of H-beam. Such alternative supports as splitset, splitshet and shotcrete will be considered to be applied by initially performing geotechnical investigations and monitoring of rock deformation by convergent measuring on the supports currently installed. To determine the class of the rock mass, classification of the empirical rock mass of Rock Mass Rating (RMR) Bieniawski, 1989, and Q-system classification were performed. The software on the basis of Finite Element Method used in this study from the 2D Phase2 Rocscience.Inc as verification of various support recommended by the rock mass classification and calculating CGT Ramp down stability with variety of alternative support. Based on the RMR89 rock mass classification, the class of the rock mass obtained from the CGT Ramp down area was that of class III (moderate rock), with its corrected total weight being 51. Estimates of rock mass cohesion = 200-300 KPa and the rock mass friction angle = 25 ° - 35°. The Q-system set the values of the rock mass quality at the CGT Ramp down as "good" with a value of Q = 20.14. As a design for alternative support and CGT Ramp down stability, 4 (four) design models were made with the following results: Model 1 (without support): it could be seen that the Ramp down was in a state of being instable or collapsed. Model 2 (support split set): Ramp down started to look safe despite unstable regions at some points. Model 3 (a combination of support split set and shotcrete): the Ramp down looked stable. Model 4 (combination of support split set and H-beam): the Ramp down looked very stable. Of all the supports that have been modeled, each has the ability to provide stability, but the splitset and H-beam supports (ones in use today) have the best stability.